"Anfisa" by L. Andreev: early theatrical productions. Pavel Samoilov as Fyodor Kostomarov (New Dramatic Theatre, 1909), Ekaterina Roshchina-Insarova as Anfisa (K. Nezlobin Theatre, 1910) - Samsonenko, Anna YUr'evna (Философия и культура, 2025)
The key figure of the "new drama" and the new theater of the 20th century is Leonid Andreyev, whose work is associated with radical innovations in directing. However, the "Theater of the Actor" remains in the shadows – the explorations undertaken by artistic individuals within the "territory" of Andreyev's dramaturgy. One such forgotten and, in essence, lost narrative in theater studies is the first productions of the play "Anfisa" (1909). Andreyev's new play particularly interested the acting theater. The first productions were carried out by private stages: the Petersburg New Dramatic Theater and the Moscow troupe of Konstantin Nezlobin. In the first performance (1909), the scenic authorship belonged to the actor Pavel Samoylov, who played the role of Fyodor Kostomarov, while in the second (1910), it was actress Ekaterina Roshchina-Insarova who performed the titular role of Anfisa. Two dissimilar stylistic artistic personalities, Samoylov and Roshchina-Insarova, presented two polar variants of Andreyev's play. In Samoylov's case, the "neurasthenic actor," the naturalistic style is clearly evident. In Roshchina-Insarova's variant, the modern actress, a new – poetic – structure of imagery is apparent, and this new imagery can be most closely associated with symbolism. Based on the reviews of contemporaries, a reconstruction of the roles has been conducted, which implies a critical approach and contextual analysis. The methodological foundation has become a complex of historical approaches, primarily the comparative-historical method. For the turn of the first decades of the 20th century, these two radically opposed interpretations of "Anfisa," the Samoylov and Roshchina versions, turn out to be more than a local phenomenon. It is precisely within the territory of Andreyev's play, which provided opportunities for such extreme interpretations, that the movement of artistic time is revealed – the change of artistic currents: it is evident that by the end of the 1900s, naturalism was a completed stage in art. Symbolism, in turn, emerges as the sought-after "new," and it is this "new" that is embodied in the individuality of the actress. It is significant that Roshchina-Insarova would become so appealing to the future directing theater (primarily for the key figure of this theater, Vsevolod Meyerhold). From the new stylistic individuality of the actress, a new stylistic construct of the performance can and should be created: as is well known, it is precisely in the category of style that different "lines" combine into a whole: artistic and historical, individual and temporal.